The female athlete triad: Are elite athletes at increased risk? - Torstveit, M. K.; Sundgot-Borgen, J. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The aim of this study was to examine the percentage of elite athletes and controls at risk of the female athlete triad.